ANALISIS TENTANG KEABSAHAN JUAL-BELI TANAH GARAPAN BEKAS TANAH PARTIKELIR VERPONDING (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR : 1870 K/PDT/2017) - Delvin Akbar; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
The agreement could emerge in many forms, in general, it could be divided into 2 forms: written agreement and unwritten agreement. In common, there are some forms of agreement that are already known by the society such as land sale and purchase, lease, and so forth, in which land sale and purchase agreement is the most known agreement. According to customary law, land sale and purchase is a land rights shifting that is clear and cash. The legal requirements of an agreement are regulated in article 1320 KUHPerdata. However, the legal requirements of land sale and purchase agreements are not considered in the verdict of District Court of Jakarta Pusat No.519/Pdt.G/2012/Pn.Jkt.Pst, the verdict of High Court of Jakarta No. 467/PDT/2015/PT.DKI and verdict of Supreme Court No : 1870 K/Pdt/2017. In this research, the researcher investigated the validity of land sale and purchase of arable land that previously exists as verponding land, which is written in the verdict of Supreme Court No : 1870 K/Pdt/2017. The method used in this research is normative law, supported by the interview data. The results of this research show that the judge has ignored legal regulations and provisions. The basic consideration of the verdicts is contradicted with the legal requirements of an agreement that is regulated in article 1320 KUHPerdata. The panel of judges should consider the validity of the land sale and purchase agreement as the basis of the verdict.